2018
DOI: 10.3389/fimmu.2018.01331
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a-5p Regulates TNF-α and miR-21a-5p Influences Gualynate-Binding Protein 5 and IL-10 Expression in Macrophages Affecting Host Control of Brucella abortus Infection

Abstract: Brucella abortus is a Gram-negative intracellular bacterium that causes a worldwide zoonosis termed brucellosis, which is characterized as a debilitating infection with serious clinical manifestations leading to severe complications. In spite of great advances in studies involving host–B. abortus interactions, there are many gaps related to B. abortus modulation of the host immune response through regulatory mechanisms. Here, we deep sequenced small RNAs from bone marrow-derived macrophages infected with B. ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…miR-181 also plays a role in inflammation. It has been shown to downregulate production of TNF-α in Brucella abortus infections (39). These data, along with ours, suggest that breastmilk miRs are likely involved in protecting infants in modulating the immune system (i.e., to reduce inflammation by infection and to impact T-cell maturation).…”
Section: Discussionsupporting
confidence: 77%
“…miR-181 also plays a role in inflammation. It has been shown to downregulate production of TNF-α in Brucella abortus infections (39). These data, along with ours, suggest that breastmilk miRs are likely involved in protecting infants in modulating the immune system (i.e., to reduce inflammation by infection and to impact T-cell maturation).…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggest that GBP5 is the molecule responsible for the phenotype observed in GBP chr3 KO mice related to caspase-11 recognition of Brucella LPS. More recently, our research group identified that miR-21a-5p led to downregulation of GBP5 expression in macrophages infected with Brucella and increased bacterial counts in macrophages [67]. This study highlights the importance of GBP5 regulation by a miRNA in macrophage susceptibility to Brucella infection.…”
Section: Discussionmentioning
confidence: 57%
“…Experimental periodontitis using systemic microbial challenge (Porphyromonas gingivalis gavage) led to distinct patterns of inflammatory and epigenetic features [128]. miR-181a-5p and miR-21a-5p influenced the expression of inflammatory mediators in macrophages infected with Brucella abortus, thus contributing to bacterial control in host cells [129]. In addition, bacterial vaginosis predicted the length of gestation through miRNA-related epigenetic programming of the inflammatory response [130].…”
Section: Infectionsmentioning
confidence: 99%